The Relationship Between Self Care and Quality of Life Among Coronary Heart Disease Patient After Receiving Percutaneous Coronary Intervention: A Systematic Review - Herdiman, .; Harsono, Heri (KnE Life Sciences, 2021)
Coronary Heart Disease is a chronic disease with the highest morbidity and mortality rates in the world. Management is needed in the form of self-care management as a core element for CHD patients in order to improve the quality of life. Until now, there has been no comprehensive summary regarding self-care and quality of life for CHD patients with stents attached. This study aims to summarize research studies that link self-care and QOL in CHD patients after receiving Percutaneous coronary intervention. Systematic review using three databases (PubMed, ScienDirect, Google Scholar) for previous studies published in the last 10 years (2010–2020). The Joana Bright Institute format and PRISMA guidelines were used to assess the quality of studies and assist in the selection of articles. Data was extracted and summarized by the author using data extraction tools from JBI. Five articles from 2,729 studies were included. The results show inconsistency, namely three studies have a significant relationship and two studies have an insignificant relationship. All questionnaire domains used in the five articles state that the self-care domain of smoking cessation and exercise are correlated with the QOL domain of physical function, body pain, vitality, mental health, symptom domains and satisfaction. Only three articles reported the strength of the relationship (r = 0.117–0.64) and two articles didn’t report the strength of the relationship. By knowing self-care and QOL of CHD patients after receiving PCI, it’s hoped that the hospital can better understand and provide promotive/preventive education related to self-care management so that the patient’s QOL increases significantly. Keywords: Self-care, quality of life, Coronary Heart Disease, Percutaneous Coronary Intervention, Systematic Review